Sistem Pendukung Keputusan Prioritas Penggunaan Dana Desa di Desa Dalu Sepuluh A menggunakan Metode Multi Factor Evolution Process (MEFP) - Muhammad Fahriat; Efori Buulolo; Saidi Ramadan Siregar (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Decision support system (DSS) is a system that can help leaders in making accurate and targeted decision. There are many problems can be solved using DSS, one of which is a decision support system for the use of village funds. At present the use off village funds is sometimes not on target so that empowermant and distribution of these funds are less effective, because the distribution still uses a manual system, where the manual system which often make it less offective.